2021
DOI: 10.1371/journal.pone.0252017
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood environmental attributes and walking mobility decline: A longitudinal ecological study of mid-to-older aged Australian adults

Abstract: Objectives Cross-sectional studies have found some built environmental attributes to be associated with residents’ lower levels of mobility (functional capacity to walk outside the home). However, less is known about what environmental attributes are related to mobility decline. This longitudinal study examined area-level associations of specific environmental attributes with mid-to-older aged adults’ changes in walking mobility. Methods Data collected from 4,088 adults (aged 46–71 years at baseline) who par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…We chose to not include detailed information on neighborhood characteristics (e.g. land use mix, street connectivity), since previous HABITAT research has shown only weak correlation with physical activity among older adults [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We chose to not include detailed information on neighborhood characteristics (e.g. land use mix, street connectivity), since previous HABITAT research has shown only weak correlation with physical activity among older adults [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…When formulating corresponding policies, the relevant departments need not give priority to the impact of mixed land use. However, considering that there were relatively few research objects included, it was still necessary to further explore the relationship between two of them ( Sugiyama et al, 2021 ).…”
Section: Disscussionsmentioning
confidence: 99%
“…Oral health is one of the key constituents of healthy ageing but is an area of practice and research that is often under prioritised [ 6 10 ]. With increasing age, a person is more likely to experience a decline in their health, have reduced functional ability and require higher dependence on informal or formal caregivers [ 11 13 ]. These factors make it more likely that an older person will require assistance to maintain good oral health [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%